Retinal Changes in Uncomplicated and Severe Plasmodium knowlesi Malaria. (15th December 2015) - Govindasamy, Gayathri; Barber, Bridget E.; Ghani, Shuaibah A.; William, Timothy; Grigg, Matthew J.; Borooah, Shyamanga; Dhillon, Bal; Dondorp, Arjen M.; Yeo, Tsin W.; Anstey, Nicholas M.; Maude, Richard J.
Abstract : Background. Plasmodium knowlesi causes severe malaria, but its pathogenesis is poorly understood. Retinal changes provide insights into falciparum malaria pathogenesis but have not been studied in knowlesi malaria. Methods. An observational study was conducted in Malaysian adults hospitalized with severe (n = 20) and nonsevere (n = 24) knowlesi malaria using indirect ophthalmoscopy (n = 44) and fundus photography (n = 29). Results. The patients' median age was 44 years (range, 18–74 years). No coma or deaths occurred. Photography detected retinal changes in 11 of 12 patients (92%) with severe and 14 of 17 (82%) with nonsevere knowlesi malaria. Nonspecific retinal whitening occurred in 3 (35%) and 5 (29%) patients with severe and nonsevere disease, respectively; hemorrhages in 2 (17%) and 3 (18%); loss of retinal pigment epithelium in 1 (8%) and 4 (24%); and drusen in 9 (71%) and 12 (75%). All changes were mild, with no significant differences between severe and nonsevere disease. Patients with retinal hemorrhages had lower platelet counts than those without (median, 22 vs 43 × 10 9 /L; P = .04). Conclusions. The paucity of specific retinal findings associated with disease severity in knowlesi malaria contrasts with the retinopathy of severe adult falciparum malaria with and without coma, suggesting that falciparum-like microvascular sequestration in the brain is not a major component in severe knowlesi malaria pathogenesis.